An Exceptionally Efficient Co−Co2P@N, P‐Codoped Carbon Hybrid Catalyst for Visible Light‐Driven CO2‐to‐CO Conversion. Issue 34 (7th June 2018) - Xu, Yong; Mo, Jiang; Fu, Zi‐Cheng; Liu, Su; Yang, Zhi; Fu, Wen‐Fu
Abstract: Artificial photosynthesis has attracted wide attention, particularly the development of efficient solar light‐driven methods to reduce CO2 to form energy‐rich carbon‐based products. Because CO2 reduction is an uphill process with a large energy barrier, suitable catalysts are necessary to achieve this transformation. In addition, CO2 adsorption on a catalyst and proton transfer to CO2 are two important factors for the conversion reaction, and catalysts with high surface area and more active sites are required to improve the efficiency of CO2 reduction. Here, a visible light‐driven system for CO2 ‐to‐CO conversion is reported, which consists of a heterogeneous hybrid catalyst of Co and Co2 P nanoparticles embedded in carbon nanolayers codoped with N and P (Co‐Co2 P@NPC) and a homogeneous Ru II ‐based complex photosensitizer. The average generation rate of CO of the system was up to 35 000 μmol h −1  g −1 with selectivity of 79.1 % in 3 h. Linear CO production at an exceptionally high rate of 63 000 μmol h −1  g −1 was observed in the first hour of reaction. Inspired by this highly active catalyst, Co@NC and Co2 P@NPC materials were also synthesized and their structure, morphology, and catalytic properties for CO2 photoreduction were explored. The results showed that the nanoparticle size, partially adsorbed H2 O molecules on the catalyst surface, and the hybrid nature of the systems influenced their photocatalytic CO2 reduction performance. Abstract : A hybrid photocatalyst consisting of Co and Co2 P nanoparticles embedded in N, P‐codoped carbon nanosheets was used in a visible light‐driven system for CO2 ‐to‐CO conversion. The catalytic system displayed a high CO production rate of up to 35 000 μmol h −1  g −1 with CO selectivity of 79.1 % in the first 3 h of reaction. Linear CO production at an exceptionally high rate of 63 000 μmol h −1  g −1 was observed in the first 1 h of photocatalytic reaction.